The Revolts of the Varangians in Constantinople: Two Incidents at the Palace - Fylypchuk, Oleksandr (Studia Ceranea, 2024)
This article deals with the revolts staged by the Varangians at the imperial palace in 1068 and 1078. The first part of the article focuses on the revolt at the beginning of Romanos IV Diogenes’s reign as described by the Continuator of Skylitzes. The detailed analysis of the chronicler’s account of the Varangians’ uprising in 1068 offers a new perspective on the relevant passage in his work. It reveals important details regarding the sources of the account in question, including its relationship with the works of Psellos and Bryennios. The author argues that the Varangians were not hostile to Romanos IV Diogenes at the beginning of his reign and that the Continuator of Skylitzes misplaced the relevant story in his narrative. The information he provided was indebted to Psellos and Bryennios. The second part of the article is devoted to the last revolt which the Varangians raised in April–May 1078. Analysis of the accounts of three historians: Michael Attaleiates, Continuator of Skylitzes, and Nikephoros Bryennios, supports the conclusion that the Continuator of Skylitzes and Bryennios recounted the first part of the story while Attaleiates (and partially the Continuator of Skylitzes) reported its end.